Modelagem e aplicação de métodos de fronteira imersa para análise de escoamentos sobre atenuadores de VIV - Carvalho, André Rezende Dessimoni (2021)
The present work addresses the use and implementation of immersed boundary methods to simulate flows over complex geometries of real problems. The work is divided into three parts. In the first part, bibliographical reviews on immersed boundary methods and on the physics of the VIV phenomenon are carried out. In the second part, the Multi-Direct Forcing (MDF) method, already implemented in the MFSim platform, is used for the simulation of fluid-structure interaction problems of cylinders equipped with strakes immersed in the ocean. The effects of different fluid dynamics and structural conditions on the dynamic behavior of structures are analyzed. Several geometric configurations of strakes are also tested, and the results are analyzed highlighting the most relevant design variables. The third part presents the specific steps of marking Eulerian points, necessary for the implementation of the Local Ghost Cells Method (LGC) in the MFSim code. A general review of the method is carried out, followed by the details of the numerical implementation of the steps and optimizations carried out in the algorithms. The implementation of the remaining parts of the Local Ghost Volumes method is part of the work of Ribeiro Neto (2021). The implementation of the LGC will provide more accurate results for flows over complex geometries, such as strakes, thus, the third part is understood as being a continuation of the second, and whose ultimate goal is to improve the simulations of the flows over strakes.